Assessing the Impact of a Virtual Shelter Medicine Rotation on Veterinary Students' Knowledge, Skills, and Attitudes Regarding Access to Veterinary Care - Hoffman, Christy L.; Spencer, Terry G.; Makolinski, Kathleen V. (Frontiers in Veterinary Science, 2021)
Strong bonds commonly form between companion animals and people of all socio-demographic backgrounds, yet many pet owners face numerous barriers to accessing veterinary care for their companion animals. For example, they may have difficulties paying for care; they may lack veterinary practices in their community; and they may experience language barriers that impede their ability to utilize veterinary services. Various strategies exist that can help veterinarians address the diverse needs of pet owners in their communities, but these techniques are not commonly covered in the veterinary school curriculum. This study explored how including in-depth, purposefully curated information about access to veterinary care issues within a required shelter medicine rotation impacted fourth-year veterinary students’ knowledge, skills, and attitudes regarding the problems clients commonly face when seeking access to veterinary care. Students participated either in a control group of a virtual, four-week rotation delivered via Zoom meetings and self-study, or in an experimental group that additionally completed an interactive online learning module. The online module heavily featured issues surrounding access to veterinary care. Irrespective of which version of the rotation students enrolled, their opinions grew more favorable from pretest to post-test regarding the role of not-for-profit veterinary clinics in communities, as did their expectations that veterinarians should provide affordable treatment options. Additionally, students in the experimental group demonstrated from pretest to post-test increased awareness of the potential for implicit bias toward pet owners within veterinary practice and showed a reduction in their tendency to be judgmental of veterinary clients. By the end of the study, students in the experimental group also expressed greater confidence in their ability to offer incremental care treatment options to veterinary clients. These findings suggest that providing content that focuses on increasing access to veterinary care enhances students’ awareness of the need to offer a variety of treatment and payment options to clients. Findings from this study can inform curriculum design in veterinary schools and continuing education programs for veterinary professionals.